Interrelationship between chronic periodontitis and anemia: A 6-month follow-up study - Megha Dhananjay Patel; Quaid Johar Shakir; Arvind Shetty (Wolters Kluwer Medknow Publications, 2014)
Background: In India, anemia is a common and serious health disorder among both sexes and all age groups, with anemia of chronic disease (ACD) being the second most prevalent anemia. Periodontitis is an inflammatory disease of the supporting tissues of the tooth caused by specific microorganisms. An immune response to bacteria and their products induces a major vascular response, offering explanatory mechanisms for the interactions between periodontal infection and a variety of systemic disorders. Therefore, periodontitis results in low-grade systemic inflammation, which may cause lower number of erythrocytes and, consequently, lower hemoglobin concentration. Materials and Methods: A total of 100 systemically healthy male patients visiting the outpatient department participated in the study. Of these, 50 patients had healthy periodontium and 50 patients had chronic periodontitis. Clinical parameters and red blood cell parameters of all the patients were assessed at baseline and 6 months after non-surgical periodontal therapy. Statistical analysis using Student's t-test was performed. Results: Data analysis revealed that patients with chronic periodontitis showed an improvement in both clinical and red blood cell parameters from baseline to 6 months after non-surgical periodontal therapy. Conclusion: From the present study, it can be concluded that like any other chronic condition, chronic periodontitis can lead to ACD. It also provides evidence that non-surgical periodontal therapy can improve the anemic status of patients with chronic periodontitis.